Dari Ibrahim M. Abu Rabiâ tentang Problematika Studi Islam Kontemporer - Mahfudh, Hasan (Institut Agama Islam Negeri (IAIN) Salatiga, 2016)
The dynamic of thought, study, and learning is a necessity. The interaction of subjectsÂ and objects, added by some problems which are being or have occurred and theÂ challenges that will be faced become the reasons for this dynamic. It is not a problemÂ if perspectives, approaches or scientific paradigm have shifted significantly later.Â Islamic study formulated in the Ulum al-din, al-Fikr al-Islamy or Dirasat Islamiyyah isÂ ideally always dynamic and evolving as a study in general. Despite of the variousÂ problems faced by Muslims today, Ibrahim M. Abu Rabi â(hereinafter typed AbuÂ Rabiâ) found no significant development of Islamic studies. Stagnation of IslamicÂ studies at least can be found in the various elements. Through the study of IslamicÂ thought history, Abu Rabiâ tried to uncover the âdiseaseâ which was lull. Then, heÂ tried to resuscitate the intellectuals to fully understand the role and function inencouraging Islamic studies with a scientific perspective developing at this time.Â The issue becoming increasingly complex cannot be explained satisfactorily by theÂ classical Ulum al-Din theory which is only focused on text, especially only a portionÂ of the text. Halal and haram for example are felt helpless facing increasingly variedÂ social problems. Islamic studies would not want to open and open up to theÂ disciplines of science, not mono-dicipline.